Exploring the Causes of Frictional Wage Dispersion - Volker Tjaden; Felix Wellschmied (University of Bonn, Bonn Graduate School of Economics (BGSE), 2011)
Standard search models are inconsistent with the amount of frictional wage dis- persion found in U.S. data. We resolve this apparent puzzle by modeling skill development (learning by doing on the job, skill loss during unemployment) and duration dependence in unemployment benefits in a random on the job search model featuring two-sided heterogeneity. The model's key parameters are calibrated using micro data on employment mobility and wages from the Survey of Income and Program Participation (SIPP). Our model is consistent with the amount of frictional wage dispersion found in the data. Skill develop- ment on the job is the most important driver behind this result. Meanwhile, firm heterogeneity never accounts for more than 20% of overall wage inequality within an age cohort.
Keywords: J24; J31; J64; 330; Frictional wage dispersion; Search model; Heterogeneity; Lohnstruktur; Qualifikation; Lernprozess; Arbeitslosigkeit; Dauer; Arbeitsuche; Theorie; Schätzung; USA